Should I Stay or Should I Go? The Role of Actuarial Reduction Rates in Individual Retirement Planning in Germany - Sebastian Kluth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper provides a two-part empirical analysis on how actuarial reduction rates for early retirement affect current pension payments in Germany and to what extent the existence and the magnitude of these reduction rates influence people s retirement planning. First, by evaluating a large dataset of administrative records it becomes evident that early retirement shows a high prevalence at the extensive and at the intensive margin, in particular for women and those with a medium income. Second, a special question in the 2011 SAVE survey is exploited where respondents are offered a hypothetical deal for early retirement if in turn they were willing to accept an actuarial reduction on their pension. It becomes evident that the maximum reduction rate people would be willing to accept is widely dispersed and on average approximately double the current legal rate. Furthermore, respondents seem to make consistent choices and high endowment of financial assets plus additional old age provision, high subjective life expectancy, bad health as well as being a man are positively correlated with the actuarial reduction rate the respondents would accept at most. Given that policymakers aim to raise the average retirement age, the results emphasize the need for a simultaneous increase of not only the statutory retirement age but the minimum early retirement age as well. This becomes necessary since actuarial reduction rates cannot be expected to change the retirement behavior of workers with a strong preference for early retirement or those who rely on social benefits.
Keywords: H55; D84; D91; 330